Governance, Local Institutions and Local Governance: A Conceptual Analysis (Global Journal of Human-Social Science, 2019)
This paper analyzed the trio of governance local institutions and local governance from conceptual perspectives It specified the analytic features of governance and local institutions as well as their conceptual reflections on local governance Specifically this paper provides a set of instructions and the ordering of governance local institutions as well as local governance in social sciences debates In general the granularity of these concepts is governed by the needs of the writers researchers However this conceptual analysis has specified them in such a degree of details that displays the interconnections and differences between them Nonetheless it does not formalize them in a conceptual framework rather it simply states the set of instructions for using them as concepts and the kind of problem motivating their applications as well as a well-known piece of philosophical research
Keywords: governance; local institutions; local governance; and conceptual analysis